Cdc7 kinase stimulates Aurora B kinase in M-phase - Ito, Sayuri; Goto, Hidemasa; Kuniyasu, Kinue; Shindo, Mayumi; Yamada, Masayuki; Tanaka, Kozo; Toh, Gaik-Theng; Sawa, Masaaki; Inagaki, Masaki; Bartek, Jiri; Masai, Hisao (Scientific reports, 2019)
The conserved serine-threonine kinase, Cdc7, plays a crucial role in initiation of DNA replication by facilitating the assembly of an initiation complex. Cdc7 is expressed at a high level and exhibits significant kinase activity not only during S-phase but also during G2/M-phases. A conserved mitotic kinase, Aurora B, is activated during M-phase by association with INCENP, forming the chromosome passenger complex with Borealin and Survivin. We show that Cdc7 phosphorylates and stimulates Aurora B kinase activity in vitro. We identified threonine-236 as a critical phosphorylation site on Aurora B that could be a target of Cdc7 or could be an autophosphorylation site stimulated by Cdc7-mediated phosphorylation elsewhere. We found that threonines at both 232 (that has been identified as an autophosphorylation site) and 236 are essential for the kinase activity of Aurora B. Cdc7 down regulation or inhibition reduced Aurora B activity in vivo and led to retarded M-phase progression. SAC imposed by paclitaxel was dramatically reversed by Cdc7 inhibition, similar to the effect of Aurora B inhibition under the similar situation. Our data show that Cdc7 contributes to M-phase progression and to spindle assembly checkpoint most likely through Aurora B activation.
Keywords: Cell Cycle; nádorové buněčné linie; Aurora Kinase B; Insecta; Rats; Aurora kinasa B; survivin; HEK293 Cells; Phosphorylation; Survivin; HeLa Cells; buněčné dělení; protein-serin-threoninkinasy; mitóza; chromozomální proteiny, nehistonové; hmyz; mutace; HCT116 buňky; Cell Division; Cell Line, Tumor; Spindle Apparatus; HCT116 Cells; Threonine; krysa rodu Rattus; Cell Cycle Proteins; buněčný cyklus; aparát dělícího vřeténka; Mitosis; Protein Serine-Threonine Kinases; proteiny buněčného cyklu; threonin; Centromere; Mutation; zvířata; HEK293 buňky; Humans; centromera; Chromosomal Proteins, Non-Histone; fosforylace; HeLa buňky; lidé; Animals